Nonlocal Peridynamic Modeling and Simulation on Crack Propagation in Concrete Structures. (23rd February 2015) - Huang, Dan; Lu, Guangda; Liu, Yiming
Abstract : An extended peridynamic approach for crack propagation analysis in concrete structures was proposed. In the peridynamic constitutive model, concrete material was described as a series of interacting particles, and the short-range repulsive force and anisotropic behavior of concrete were taken into account in the expression of the interactive bonding force, which was given in terms of classical elastic constants and peridynamic horizon. The damage of material was defined locally at the level of pairwise bond, and the critical stretch of material bond was described as a function of fracture strength in the classical concrete failure theory. The efficiency and accuracy of the proposed model and algorithms were validated by simulating the propagation of mode I and I-II mixed mode cracks in concrete slabs. Furthermore, crack propagation in a double-edge notched concrete beam subjected to four-point load was simulated, in which the experimental observations are captured naturally as a consequence of the solution.